Characteristics of drug-facilitated sexual assault (DFSA) : an observational study at a Danish sexual assault center - Rasmussen, Marina; Busch, Johannes Rødbro; Munkholm, Julie; Skov, Kathrine Østerballe; Nielsen, Marie Katrine Klose; Hilden, Malene; Banner, Jytte; Wingren, Carl Johan (International Journal of Legal Medicine, 2025)
INTRODUCTION: In drug facilitated sexual assault (DFSA) the victim is unable to consent to the sexual act due to influence of alcohol, narcotics, or medicine. Increasing the awareness of characteristics associated with DFSA can assist the judicial system in early recognition of cases and guide public health interventions for reducing DFSA. This study aims to assess characteristics of DFSA victims compared to victims of non-DFSA. METHODS: We included 643 females from the age of 15, examined at Center for Victims of Sexual Assault (CVSA), Copenhagen, Denmark from 2021 to 2023. We extracted information on context of the case, findings of the examination, and linked register data, including socioeconomics, criminal records, and prescribed medication. We applied descriptive statistics and logistic regression models. RESULTS: DFSA victims, compared to non-DFSA, were younger and the risk was higher during weekends, at night, and by a perpetrator met for the first time the day of the assault. DFSA was associated with occurring at a public place, or the home of a friend. More injuries were observed in cases examined within 24 h of the assault. Ethanol, cocaine, and THC were the most frequent substances. Victims of sexual assault under 18 years have more reports to child protection services compared to the general population. CONCLUSION: In inebriated, young victims with memory loss, stating an assault at a public place the concern for DFSA should be raised. Early in the investigation of sexual assaults, forensic examination should be prioritized for securing samples for toxicology and documenting injuries.
© 2025. The Author(s).